COISA: A Compact OpenISA virtual platform for IoT devices - Millani, Carlos Eduardo; Linhares, Alisson; Auler, Rafael; Borin, Edson (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2015: Anais do XVI Simpósio em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/wscad.2015.14271, 2015)
In face of the high number of different hardware platforms that we need to program in the Internet-of-Things (IoT), Virtual Machines (VMs) pose as a promising technology to allow a program once, deploy everywhere strategy. Unfortunately, many existing VMs are very heavy to work on resourceconstrained IoT devices. We present COISA, a compact virtual platform that relies on OpenISA, an Instruction Set Architecture (ISA) that strives for easy emulation, to allow a single program to be deployed on many platforms, including tiny microcontrollers. Our experimental results indicate that COISA is easily portable and is capable of running unmodiﬁed guest applications in highly heterogeneous host platforms, including one with only 2 kB of RAM.